Belize’s 2016–17 Sovereign Debt Restructuring – Third Time Lucky? - Tamon Asonuma; Michael G. Papaioannou; Eriko Togo; Bert van Selm (Journal of Banking and Financial Economics)
This paper examines the causes, process, and outcome of Belize’s 2016–17 sovereign debt restructuring – its third episode in last 10 years. As was the case in the earlier two restructurings, in 2006–07 and in 2012–13, the 2016–17 debt restructuring was executed through collaborative engagement with creditors outside an IMF-supported program. While providing liquidity relief and partially addressing long-term debt sustainability concerns, the restructuring will need to be underpinned by ambitious fiscal consolidation and growth-enhancing structural reforms to secure durable gains and avoid future debt distress situations.